Gut Commensal-Induced IκBζ Expression in Dendritic Cells Influences the Th17 Response - Michaelis, Lena; Treß, Marcel; Löw, Hanna-Christine; Klees, Johanna; Klameth, Christian; Lange, Anna; Grießhammer, Anne; Schäfer, Andrea; Menz, Sarah; Steimle, Alex; Schulze-Osthoff, Klaus; Frick, Julia-Stefanie (Frontiers in Immunology, 2021)
Intestinal commensal bacteria can have a large impact on the state of health and disease of the host. Regulation of Th17 cell development by gut commensals is known to contribute to their dichotomous role in promoting gut homeostasis and host defense, or development of autoimmune diseases. Yet, the underlying mechanisms remain to be fully elucidated. One candidate factor contributing to Th17 differentiation, and the expression of which could be influenced by commensals is the atypical nuclear IκB protein IκBζ. IκBζ acts as a transcriptional regulator of the expression of Th17-related secondary response genes in many cell types including dendritic cells (DCs). Insights into the regulation of IκBζ in DCs could shed light on how these immune sentinel cells at the interface between commensals, innate and adaptive immune system drive an immune-tolerogenic or inflammatory Th17 cell response. In this study, the influence of two gut commensals of low (Bacteroides vulgatus) or high (Escherichia coli) immunogenicity on IκBζ expression in DCs and its downstream effects was analyzed. We observed that the amount of IκBζ expression and secretion of Th17-inducing cytokines correlated with the immunogenicity of these commensals. However, under immune-balanced conditions, E. coli also strongly induced an IκBζ-dependent secretion of anti-inflammatory IL-10, facilitating a counter-regulative Treg response as assessed in in vitro CD4+ T cell polarization assays. Yet, in an in vivo mouse model of T cell-induced colitis, prone to inflammatory and autoimmune conditions, administration of E. coli promoted an expansion of rather pro-inflammatory T helper cell subsets whereas administration of B. vulgatus resulted in the induction of protective T helper cell subsets. These findings might contribute to the development of new therapeutic strategies for the treatment of autoimmune diseases using commensals or commensal-derived components.